2015
DOI: 10.1590/s1679-45082015ao3251
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of maltodextrin intake 2 hours before cholecystectomy by laparotomy in respiratory function and functional capacity: a prospective randomized clinical trial

Abstract: Objective:To evaluate the change in respiratory function and functional capacity according to the type of preoperative fasting.Methods:Randomized prospective clinical trial, with 92 female patients undergoing cholecystectomy by laparotomy with conventional or 2 hours shortened fasting. The variables measured were the peak expiratory flow, forced expiratory volume in the first second, forced vital capacity, dominant handgrip strength, and non-dominant handgrip strength. Evaluations were performed 2 hours before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…A recent review of studies showed that the abbreviation of preoperative fasting with a drink enriched with carbohydrates or carbohydrates and glutamine proved to be effective in the care of surgical patients, optimizing the recovery of the postoperative period. Abbreviation of preoperative fasting time with ingestion of maltodextrin solution is beneficial to pulmonary function and preserves dominant handgrip strength [38,39].…”
Section: Prospective Randomized Clinical Trial Conducted In a Brazilianmentioning
confidence: 99%
“…A recent review of studies showed that the abbreviation of preoperative fasting with a drink enriched with carbohydrates or carbohydrates and glutamine proved to be effective in the care of surgical patients, optimizing the recovery of the postoperative period. Abbreviation of preoperative fasting time with ingestion of maltodextrin solution is beneficial to pulmonary function and preserves dominant handgrip strength [38,39].…”
Section: Prospective Randomized Clinical Trial Conducted In a Brazilianmentioning
confidence: 99%
“…The preoperative fasting time also influences functional parameters, such as the strength of the palmar grip determined by dynamometry, an indicator of postoperative complications related to worsening of functional status during hospitalization 19 , 31 . In a study conducted by Zani et al 31 patients who received carbohydrate solution, 6 h (400 ml) and 2 h (200 ml) before the surgical procedure containing 50 g and 25 g of maltodextrin, respectively, presented higher values ​​of the strength of palmar grip, both in the dominant and in the non-dominant hand. According to these authors, the group that received the intervention showed a significant improvement in respiratory function, assessed by the peak of expiratory flow in the first second and greater forced vital capacity, in comparison to the group that remained fast.…”
Section: Resultsmentioning
confidence: 99%
“…( 21 ) The literature shows that fasting is harmful and that a dietary intake, even if only liquid, can improve HGS. ( 23 , 24 )…”
Section: Discussionmentioning
confidence: 99%